RETRACTED AND REPLACED: Minimal extra-cardiac atherosclerosis present in young people with sudden cardiac death due to coronary artery disease - Elizabeth D Paratz; Louise Fahy; Ziad Nehme; Andreas Pflaumer; Dion Stub; Andre La Gerche (European Journal of Preventive Cardiology, 2025)
This article has been retracted and replaced. Please see https://doi.org/10.1093/eurjpc/zwaf622 for details. The replacement article can be found at https://doi.org/10.1093/eurjpc/zwaf615.